Renal engineering: Strategies to address the problem of the ureter. (December 2021) - Davies, Jamie A.; Elhendawi, Mona; Palakkan, Anwar A.; Sallam, May
Abstract: Current techniques for making renal organoids generate tissues that show function when transplanted into a host, but they have no ureter through which urine can drain. There are at least 4 possible strategies for adding a ureter: connecting to the host ureter; inducing an engineered kidney to make a ureter; making a stem cell–derived ureter; and replacement of only damaged cortex and outer medulla using remaining host calyces, pelvis and ureter. Here, we review progress. Local BMP4 can induce a collecting duct tubule to become a ureter; a urothelial tube can be produced directly from pluripotent cells, and connect to the collecting duct system of a renal organoid; it is possible to graft Embryonic Stem (ES) cell-derived ureters into host kidney rudiments and see connection, smooth muscle development and spontaneous contraction, but this has not yet been achieved with all components being derived from ES cells. Remaining problems are discussed.